The validation of the greek version of delirium observation scale (DOS) in cardiac patients - Evangelou, X.; Lambrinou, Ekaterini; Michaelides, C.; Middleton, Nicos (My University, 2016)
Introduction: Delirium is an acute neuropsychiatric syndrome that occurs very often in clinical settings. It is a common post-operative complication with 3-52% incidence in cardiac patients. The consequences of delirium include higher morbidity and mortality, lengthened hospital stay and higher cost of care. Although there is a plethora of screening tools, delirium is difficult to diagnose and is often missed, due to different clinical expressions.The need for use of standardized and valid screening tools is major, as well as the finding and implementation of effective dealing strategies.Aim:The aim of this study is the validation of the Greek version of Delirium Observation Scale (DOS) in cardiac patients.Material and Method: This is a methodology study of investicating the validation and predictictability of the Greek version of DOS in Greek-Cypriot cardiac patients. Reliability and internal validity were evaluated with Cronbach’s Alpha coefficient. Predictive validity was evaluated with the diagnosis of a neurologist according to DSM-IV criteria which is considered to be the “gold standard”.Results: Cronbach’s Alpha was 0.98, kappa measure of agreement was 1.00, giving both 100% sensitivity and speciality to the tool.Conclusion: DOS is a valid, useful and friendly tool for nurses to identify delirium in cardiac patients.
Keywords: Delirium Observation Scale; Patients; DOS